Utrata cienia – fragmenty „włoskiej biografii” Gustawa Herlinga-Grudzińskiego - Śniedziewska, Magdalena (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
In Journal Written at Night Gustaw Herling analyzes the Peter Schlemihl’s Miraculous Story by Adelbert von Chamisso. The Polish writer (as an émigré) is extremely sensitive to the fate of artists forced to live away from their birthplace and, unlike Thomas Mann, proposes an interpretation according to which the loss of a shadow means the lack of homeland. Herling understands breaking away from his homeland as a kind of physical handicap: an existence without native land. However, if the roots can be found in another soil, it is impossible to regain the shadow. Herling introduces the distinction between hard existence and indeterminacy of feelings of a man eradicated, combining the alienation experienced in Naples with an intangible, but also irreversible loss of a shadow.